Implementation of Change Management and Innovation in Improving Higher Education Institution’s Performance in Indonesia - Paidi, Paidi; Diandra, Didip; Priyono, Agung; Sulistianto, Hario; Syahputra, Erwin (Universitas Islam Kadiri, 2024)
Higher Education Institution (HEI) in Indonesia plays an important role as central position in the development of science and technology in general and the improvement of human resources in particular. Rapid change in the world current economic condition and else digital technology transformation has tend the higher education to adapt and adjust with such phenomenon. The objective of this research is to remind the practitioners of higher education sector to be fully responsive to the change occurred in global. The research method is analytical descriptive analysis. The data gathered and obtained from the books, journals, and other sources which relevant to the topic of research. The result of analysis found that quick anticipation (QA) is required and top management of higher education must adopt change management and innovation in order to compete with others, attract the students, and gain excellence performance.